Social networks and household financial decisions: Evidence from China - Mingming Jiang; Rongrong Sun; Bo Zhang (Journal of Applied Economics, 2022)
Based on three waves of a nationwide household survey in China, we demonstrate that social networks facilitate household financial market participation and risky asset holding. By constructing an index that considers various dimensions of social networks, our extensive empirical analysis suggests that a higher value of the social network index significantly increases the probability of a household's market participation and the fraction of risky assets holding in both formal and informal financial markets. This finding is robust across different waves of survey data; it is also robust to alternative index construction, estimation techniques, and variable definitions. We derive explicit expressions for the coefficients and standard errors of the interaction effects in the Probit and Tobit models and reveal that the impact of social networks is transmitted to household financial decisions through two channels: an information channel and a risk-sharing channel.
Keywords: 330; asset allocation; financial market participation; Social networks